2016
DOI: 10.4187/respcare.04471
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Ventilatory Inefficiency and Exercise Capacity in Idiopathic Pulmonary Fibrosis

Abstract: BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and fatal interstitial lung disease associated with poor prognosis and limited effective treatment options. Reliable predictors of outcome in daily clinical practice are needed to determine high-risk patients for urgent lung transplantation referral. This study aimed to identify practical prognostic predictors of mortality using cardiopulmonary exercise testing (CPET) in IPF subjects. METHODS: Thirty-four subjects with IPF (22 men and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…A prospective observational study evaluating 25 IPF patients, observed for a period of 9-64 months, showed that V′E/V′CO 2 slope and V′O 2 peak rate per kg had the strongest correlation with survival [77]. Impairment in exercise capacity and abnormal ventilatory responses during CPET were confirmed to be associated with poorer survival in a study recently performed in 34 IPF subjects who were followed-up for 40 months [78]. A multicentre retrospective study to predict 3-year mortality was completed on 63 adult patients with IPF who underwent CPET with blood gas analysis [79].…”
Section: The Role Of Cardiopulmonary Exercise Test In Ildsmentioning
confidence: 89%
“…A prospective observational study evaluating 25 IPF patients, observed for a period of 9-64 months, showed that V′E/V′CO 2 slope and V′O 2 peak rate per kg had the strongest correlation with survival [77]. Impairment in exercise capacity and abnormal ventilatory responses during CPET were confirmed to be associated with poorer survival in a study recently performed in 34 IPF subjects who were followed-up for 40 months [78]. A multicentre retrospective study to predict 3-year mortality was completed on 63 adult patients with IPF who underwent CPET with blood gas analysis [79].…”
Section: The Role Of Cardiopulmonary Exercise Test In Ildsmentioning
confidence: 89%
“…As mentioned previously, predictive models of IPF prognosis rely on numerous clinical factors, physiologic parameters, radiologic features, biomarkers, and pathologic findings 511,17,18 . Most models developed to date are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight IPF subjects treated in the Pulmonary Institute were screened for eligibility, and 34 subjects volunteered and were recruited for participation in the study based on 10% expected dropouts reported in a previous ILD training study [17]. We have previously reported that at 30-months and at 40-months follow-up, group allocation did not affect survival in this group of subjects; however, the sample size was underpowered to detect such changes [18,19]. Demographic characteristics were obtained from all subjects and evaluation for dyspnea by the modified Medical Research Council (mMRC) scale was made [20,21].…”
Section: Methodsmentioning
confidence: 99%